Studi Morfologi Genera Penggerek Buah Kopi (PBKo) Robusta dan Arabika serta Kerusakan yang Ditimbulkan - Harli A Karim; Frederik Deppara'ba; Juniati L; Hikmahwati Hikmahwati (Universitas Sebelas Maret, 2025)
Coffee is a strategic plantation commodity with increasing global demand. However, its productivity remains relatively low due to pest and disease infestations. One of the major pests causing substantial yield losses is the coffee berry borer (CBB), with infestation levels reaching 50–60% and yield reductions of 25–49%. This study aimed to identify the genera of CBB based on morphological characteristics. Infested coffee berries were collected from the field, followed by laboratory observations and morphological identification using the methods of Browne and Le Pelly. The morphological data were then compared with insect specimens from the collection of the Centre for Agriculture and Bioscience International (CABI). The results revealed morphological differences between the CBB specimens collected from the field and those of the Hypothenemus genus in the CABI collection. Three genera were identified Hypothenemus, Chryphalus, and Stephanoderes, each exhibiting distinct morphological features. The Hypothenemus imago is dark black with a three-segmented antenna ending in a rounded club; Chryphalus has a slightly black coloration, an elliptical head crown extending backward, a very small body size (<1 mm), and a soft, fragile texture; whereas Stephanoderes shows light to dark brown coloration, a prominent mouthpart resembling a shrimp head, a four-segmented antenna with a cylindrical tip, and evenly aligned setae on the wing surface. The intensity of infestation varied among the genera: Hypothenemus caused 35–77% damage in Robusta coffee, Chryphalus 10–25% in Robusta coffee, and Stephanoderes 33–50% in Arabica coffee.